Epidemiological characteristics of adenovirus in children in Yancheng, China, 2023-2024 - Guoqing Chen; Jin Cao; Jin Cao; Yingli Qu; Wenyan Tian; Peng Shen; Xuan Liu; Qin Luo; Qinqin Song; Qi Wen; Guangyu Xue; Yuting Hu; et al. (Frontiers in Cellular and Infection Microbiology)
ObjectiveTo understand the epidemiology and evolutionary characteristics of human adenovirus (HAdV) infecting children in Yancheng, China, during the winter of 2023-2024.MethodsHAdV-positive throat swab samples were collected from pediatric patients in Yancheng. The Hexon, Penton base, and Fiber genes were amplified and sequenced for typing and phylogenetic analysis of HAdV.Results170 HAdV-positive samples were collected and identified from children with acute respiratory infection (ARI) in Yancheng. A total of 133 samples were successfully amplified and sequenced for Hexon, Penton base, and Fiber genes. Phylogenetic analysis showed that HAdV-B3 was the dominant circulating strain, and two strains of B21, one strain of C1 and one strain of C5 were also identified.ConclusionDuring the winter of 2023-2024, HAdV infecting children in Yancheng was mainly the B3 type.